Monitoring Autophagy in the Model Green Microalga Chlamydomonas reinhardtii - María Esther Pérez-Pérez; Inmaculada Couso; Luis G. Heredia-Martínez; José L. Crespo (Cells, 2017)
Autophagy is an intracellular catabolic system that delivers cytoplasmic constituents and organelles in the vacuole. This degradative process is mediated by a group of proteins coded by autophagy-related (ATG) genes that are widely conserved from yeasts to plants and mammals. Homologs of ATG genes have been also identified in algal genomes including the unicellular model green alga Chlamydomonas reinhardtii. The development of specific tools to monitor autophagy in Chlamydomonas has expanded our current knowledge about the regulation and function of this process in algae. Recent findings indicated that autophagy is regulated by redox signals and the TOR network in Chlamydomonas and revealed that this process may play in important role in the control of lipid metabolism and ribosomal protein turnover in this alga. Here, we will describe the different techniques and approaches that have been reported to study autophagy and autophagic flux in Chlamydomonas.